Heidegger’s Interpretation of the Mathéma-Character of the Science - Novák, Aleš (Teorie vědy / Theory of Science, 2010)
In the mid 30s of the 20th century Martin Heidegger (1889–1976) attempted to explain the “history of Being” leading to what he called “the oblivion of Being”. In this he focused on the impact of the modern science, which he grants to be a sort of metaphysics. According to Heidegger, the main feature of the modern science consists in what he calls the mathéma-character. The Greek word “to mathéma” means “it what can be learned” and “what must be know beforehand”. It is Heidegger’s intention to show that the mathéma-character of the modern science is deciding about the general understanding of the meaning of “being” and that modern science is replacing the metaphysics, which is the origin of the modern science.